2008
DOI: 10.2500/ajr.2008.22.3136
|View full text |Cite
|
Sign up to set email alerts
|

Th2 Cytokines associated with Chronic Rhinosinusitis with Polyps Down-Regulate the Antimicrobial Immune Function of Human Sinonasal Epithelial Cells

Abstract: Background-Chronic rhinosinusitis with nasal polyps (CRSwNPs) is a disorder characterized by persistent eosinophilic Th2 inflammation and frequent sinonasal microbial colonization. It has been postulated that an abnormal mucosal immune response underlies disease pathogenesis. The relationship between Th2 inflammatory cytokines and the innate immune function of sinonasal epithelial cells (SNECs) has not been explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
97
3
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 31 publications
6
97
3
1
Order By: Relevance
“…It has been suggested that an ineffective local Th1-based immune response in these patients is asso ciated with increased Th2-cytokine-based activity, which contributes to a chronic infection as well as to an increased presence of eosinophils, which then lead to further polyp formation (5). It has been further proposed that the weakened Th1 response in these patients may be secondary to the down-regulation of some specific toll-like receptors involved in the innate immune response (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that an ineffective local Th1-based immune response in these patients is asso ciated with increased Th2-cytokine-based activity, which contributes to a chronic infection as well as to an increased presence of eosinophils, which then lead to further polyp formation (5). It has been further proposed that the weakened Th1 response in these patients may be secondary to the down-regulation of some specific toll-like receptors involved in the innate immune response (5).…”
Section: Introductionmentioning
confidence: 99%
“…It has been further proposed that the weakened Th1 response in these patients may be secondary to the down-regulation of some specific toll-like receptors involved in the innate immune response (5).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that Th2 cytokines downregulate toll-like receptors (TLR) expression and inhibit TLR signaling function in Th1 lymphocytes membrane. Thus, Th2 cytokines inhibit Th1 cytokines production resulting in down-regulation of antimicrobial mucosal immunity [4]. Hamilos et al [20] found significantly higher levels of IL-5 in nasal polyp tissue from asthmatic than those from nonasthmatic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The initiating factor that underlie persistent inflammation and microbial colonization in NP are not well understood. Although Th2 inflammation is a central characteristic of the disease process, what triggers the local production of Th2 cytokines and infiltration of eosinophils and lymphocytes is unknown [4]. It has been shown that Th2 cytokines downregulate toll-like receptors (TLR) expression and inhibit TLR signaling function in Th1 lymphocytes membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation